2020
DOI: 10.1002/ehf2.13024
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin inhibits Na+/H+ exchanger activity in human atrial cardiomyocytes

Abstract: Aims Recent clinical trials have proven gliflozins to be cardioprotective in diabetic and non-diabetic patients. However, the underlying mechanisms are incompletely understood. A potential inhibition of cardiac Na + /H + exchanger 1 (NHE1) has been suggested in animal models. We investigated the effect of empagliflozin on NHE1 activity in human atrial cardiomyocytes. Methods and results Expression of NHE1 was assessed in human atrial and ventricular tissue via western blotting. NHE activity was measured as the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 24 publications
2
35
0
1
Order By: Relevance
“…Secondly, we (5, 6) and others (9)(10)(11) found evidence that SGLT2i's may, at least partly, mediate their direct cellular effects through NHE-1 inhibition. A similar NHE-1 inhibition by empagliflozin was recently observed for human failing heart cardiomyocytes (12). SGLT2i inhibition of NHE results in intracellular ion changes of Na + and Ca 2+ (5,6) that may precipitate in changes in mitochondrial function (13) and can reprogram cardiac metabolism (14).…”
Section: Introductionsupporting
confidence: 64%
“…Secondly, we (5, 6) and others (9)(10)(11) found evidence that SGLT2i's may, at least partly, mediate their direct cellular effects through NHE-1 inhibition. A similar NHE-1 inhibition by empagliflozin was recently observed for human failing heart cardiomyocytes (12). SGLT2i inhibition of NHE results in intracellular ion changes of Na + and Ca 2+ (5,6) that may precipitate in changes in mitochondrial function (13) and can reprogram cardiac metabolism (14).…”
Section: Introductionsupporting
confidence: 64%
“…In follow-up studies from these same investigators, in-situ molecular modeling demonstrated that empagliflozin, dapagliflozin, and canagliflozin all favorably bind the NHE at the extracellular Na + -binding site, leading to an inhibition of NHE activity (Uthman et al, 2018). These findings have also recently been recapitulated in human atrial cardiac myocytes exposed to 1 µM empagliflozin, with the level of NHE inhibition being comparable to that observed with 10 µM cariporide (Trum et al, 2020). Taken together, the completed preclinical studies to date suggest that SGLT2 inhibitors positively influence multiple factors strongly associated with improvements in diastolic function in T2DM, and possibly through a combination of indirect on-target and direct off-target effects.…”
Section: Sglt2 Inhibitors and Diabetic Cardiomyopathy In Preclinical mentioning
confidence: 73%
“…It is still unclear, if the observed increase of NHE1 activity in heart failure is due to an increase in channel expression, posttranslational modification of the channel, or both. We have recently reported that NHE1 expression is markedly upregulated in ventricular tissue of patients with end-stage heart failure as compared to patients with left ventricular hypertrophy and normal systolic function [ 15 ]. Intriguingly, NHE1 expression has also been shown to be upregulated in the failing right ventricles of a rat model of pulmonary hypertension [ 62 ].…”
Section: Cardiac Na + Handlingmentioning
confidence: 99%
“…Therefore, many (pre-) clinical trials were performed to gain further mechanistic insights. Consequently, a myriad of potential mechanisms was proposed including direct cardiac effects such as inhibition of cardiac Na + /H + exchanger 1 (NHE1) [ 13 , 14 , 15 ], Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) [ 10 , 16 ], and late Na + current (late I Na ) [ 17 ]. Intriguingly, these proteins are centrally involved in cardiac Na + homeostasis, which is fundamentally disrupted in heart failure [ 18 , 19 , 20 ], making it an interesting target for heart failure treatment.…”
Section: Introductionmentioning
confidence: 99%